American Atrocity : The Types of Violence in Lynching - Lancaster, Guy, 1976- (Book collections on Project MUSE., 2021)
"Drawing from the fields of history, philosophy, cognitive science, sociology, and literary theory, and quoting chilling contemporary accounts, historian Guy Lancaster argues that the act of lynching encompasses five distinct but overlapping types of violence"--